Construction of a strategic change management model to enable the evolution of a high-tech enterprise - Makedon, Viacheslav; Pavlov, Dmytro; Plakhotnik, Olena; Nechaev, Dmytro; Kovnir, Oleg (Eastern-European Journal of Enterprise Technologies, 2025)
This study focuses on the process of strategic change management at a high-tech enterprise. The task addressed relates to the lack of a unified pedagogical method for managing the strategy of changes, which would combine situation analysis, diagnostics of the structure of enterprise functions, and economic-mathematical prediction of the effectiveness of transformation decisions. The main results are as follows. It has been proven that the success of transformations does not depend on individual management decisions but on a set of organizational resilience factors that help the enterprise adapt innovative processes to changes in the external environment. In the process of studying, a conceptual model of change management was built, which allows for the coordination of environment monitoring, situational diagnostics of structural inconsistencies, and the design of organizational shifts in a single management circuit. The economic-mathematical assessment was performed on the basis of data on the activities of TOV "Flight Control" in 2015–2024 using regression-correlation analysis. A statistically significant impact of internal functional subsystems on the integrated performance indicator, the overall profitability of the enterprise, which increased from 9.3% in 2015 to 13.6% in 2024, was revealed. The modeling results showed that the greatest positive impact on profitability is exerted by controlling and risk management (β = 39.55), innovation and R&D (β = 26.53), marketing and foreign contracts (β = 25.99), while financing of innovation projects without proper administrative support is characterized by a negative impact (β = –28.74). Correlation analysis (r = 0.86–0.98) confirmed the systemic relationship of management factors, which justifies the appropriateness of a comprehensive, rather than a separate, approach to strategic changes. The results could be used by enterprises in the high-tech sector to carry out structural and organizational changes, devise reorganization programs, optimize production and business processes, as well as to increase the level of innovative development